PSV-17 Association of post mortem lung health to blood serum chemistry and carcass characteristics in Holstein steers. (7th December 2018) - Francis, F; Herrick, R; Richeson, J; Lawrence, T
Abstract: Bovine respiratory disease poses a remarkable economic challenge to the fed beef population via morbidity, mortality, decreased growth, and reduced carcass quality. Our objective was to explore the association of lung health observed at slaughter to blood serum chemistry and carcass characteristics in Holstein steers (n = 52). Blood samples were collected at exsanguination, chilled, and centrifuged; serum was saved and frozen until analysis. Serum analysis provided outcomes for albumin, alkaline phosphatase, alanine aminotransferase, aspartate aminotransferase, blood urea nitrogen, Ca, Cl, globulin, glucose, K, Na, total bicarbonate, total bilirubin, and total protein. Hot carcass weight, 12 th rib subcutaneous fat thickness, ribeye area, yield grade, and marbling score were determined via camera grading. Cattle were segregated into 4 groups by severity of lung consolidation (CON; 0=50%). Interlobular fibrin (FIB) connective tissue was also assessed (none, minor, extensive). Outcomes were analyzed using a mixed model; fixed effects were CON or FIB and random effects included date, source, and pen. Blood urea nitrogen tended ( P = 0.06) to differ across FIB scores (extensive = 12.8; minor =12.1; none = 11.0 mg/dL). Hot carcass weight differed ( P = 0.01) between extensive (361 kg) and minor (409 kg) FIB scores. Creatinine differed ( P = 0.02) between 0 CON and all other CON scores (0 = 1.5, 1 = 1.3, 2 = 1.2, 3 = 1.3 mg/dL). Sodium differed ( P ≤ 0.01) between 0 CON and all other CON scores (0 = 141.2, 1 = 147.4, 2 = 145.9, 3 = 146.7 mmol/dL). These data suggest that blood urea nitrogen, creatinine, and Na levels may be associated with lung health of cattle observed at slaughter.